Economic profitability of lettuce cultivation under different cropping systems and types of fertilizers - Lacerda, Rodolfo Rodrigo de Almeida; Costa, Caciana Cavalcanti; Ferreira, Jean Telvio Andrade; Paiva, Laiza Gomes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The consortium of vegetables combined with the use of organic compounds as a source of nutrients has been widely used and has proved to be efficient when used as such. However, to avoid compromising the productive process, an economic analysis is necessary. The objective of this work was to evaluate the economic profitability of the lettuce crop in a consortium and monoculture system in function of different types of fertilizers. The experiment was conducted under field conditions at the Centro de Ciências e Tecnologia Agroalimentar of the Federal University of Campina Grande, Pombal municipality, Paraíba state. The experimental design was a randomized block consisting of three types of fertilization and two systems of cultivation, in a 3x2 factorial scheme. The first factor was three fertilizations: 1 = Fertilization with Animal Residue (Cattle manure); 2 = Mineral Fertilization; 3 = Incorporation of spontaneous vegetation and in the second factor two cropping systems: 1 = Intercropping and 2 = monoculture. In the different systems were measured the productivity, total operational cost (TOC), gross revenue, net revenue, rate of return and profitability index, in addition to the efficient use of land (UET). The highest yields were promoted by lettuce cultivation in the treatment of bovine manure in both systems with 16,450.00 and 13,160.00 kg ha-1 for monoculture and Intercropping respectively. The best yields by the Profitability Index were also observed in lettuce culture when submitted to cattle manure in both systems with values of 88.73% and 88.28% for monoculture and Intercropping respectively.